1989
DOI: 10.1093/oxfordjournals.humrep.a136832
|View full text |Cite
|
Sign up to set email alerts
|

The CA 125 tumour-associated antigen: a review of the literature

Abstract: CA 125 is an antigenic determinant on a high-molecular-weight glycoprotein recognized by a monoclonal antibody which was raised using an ovarian cancer cell line as an immunogen. During the last 5 years the studies reviewed in this paper have provided information concerning the nature, distribution and clinical significance of CA 125. The CA 125 determinant is expressed by epithelial ovarian tumours and various other pathological and normal tissues of Müllerian origin. The function of the glycoprotein expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
511
0
33

Year Published

1993
1993
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 817 publications
(560 citation statements)
references
References 0 publications
16
511
0
33
Order By: Relevance
“…Consequently, both markers had poor sensitivity for disease at second-look surgery (Table III). CA125 had a sensitivity of 53%, similar to values quoted in the literature (Jacobs & Bast, 1989), while HMFG2 had a sensitivity of 50% for disease at second-look. Recently, Moscovic et al (1991) found the sensitivity of CA125 to be better than CT scanning prior to second-look surgery.…”
Section: Resultssupporting
confidence: 83%
“…Consequently, both markers had poor sensitivity for disease at second-look surgery (Table III). CA125 had a sensitivity of 53%, similar to values quoted in the literature (Jacobs & Bast, 1989), while HMFG2 had a sensitivity of 50% for disease at second-look. Recently, Moscovic et al (1991) found the sensitivity of CA125 to be better than CT scanning prior to second-look surgery.…”
Section: Resultssupporting
confidence: 83%
“…4 The estimated PPV of a similar screening test applied annually to the general population in the United States is lower (14%) because of the slightly higher prevalence of disease observed in the UKCTOCS trial compared with the ovarian cancer incidence in the United States, which was modeled as reported by SEER. Although a PPV >10% often is considered desirable, 32 the costs associated with achieving this may be considerable when applying a multimodality algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is a need to detect ovarian cancer when it is suffi ciently small to be curable by existing therapies (1) . Cancer antigen 125 (CA 125) in serum has a high sensitivity for ovarian cancer, but CA 125 levels are frequently elevated in women with benign gynecological diseases, resulting in a reduced specifi city of this marker, especially in premenopausal women (2,3) . Therefore, there is a need for additional markers that can complement CA 125, both for early detection and differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%